Methodology for a World Bank Human Capital Index - Kraay, Aart (The World Bank, 2018)
This paper describes the methodology for a new World Bank Human Capital Index (HCI). The HCI combines indicators of health and education into a measure of the human capital that a child born today can expect to obtain by her 18th birthday, given the risks of poor education and health that prevail in the country where she lives. The HCI is measured in units of productivity relative to a benchmark of complete education and full health, and ranges from 0 to 1. A value of x on the HCI indicates that a child born today can expect to be only X x 100 percent as productive as a future worker as she would be if she enjoyed complete education and full health. The methodology of the HCI is anchored in the extensive literature on development accounting